2015
DOI: 10.7314/apjcp.2015.16.10.4251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Gene Modules in Mouse Lung Tissue Exposed to Cigarette Smoke

Abstract: Background: Exposure to cigarette may affect human health and increase risk of a wide range of diseases including pulmonary diseases, such as chronic obstructive pulmonary disease (COPD), asthma, lung fibrosis and lung cancer. However, the molecular mechanisms of pathogenesis induced by cigarettes still remain obscure even with extensive studies. With systemic view, we attempted to identify the specific gene modules that might relate to injury caused by cigarette smoke and identify hub genes for potential ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is extremely useful for data mining to identify and evaluate new hypotheses. Various publications using such databases have been reported to identify novel pathway(s) or molecule(s) as new targets for treatment and prediction of cancer (20)(21)(22). One limitation of microarray database is that the use of cross platform analysis is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…It is extremely useful for data mining to identify and evaluate new hypotheses. Various publications using such databases have been reported to identify novel pathway(s) or molecule(s) as new targets for treatment and prediction of cancer (20)(21)(22). One limitation of microarray database is that the use of cross platform analysis is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al had con rmed that UPR play a role in oncogenic transformation and involved in the network of oncogene and tumor suppressor genes to affect the progression of lung cancer [30]. Protein misfolding took place in endoplasmic reticulum (ER) can trigger ER stress and result in UPR to ER, which was took part in the development of various cancers [31]. KEGG and GO function analysis for smoking module also exhibited pathway or function about ER, for example protein processing in ER, retrograde protein transport, ER to cytosol, and ER chaperone complex, which might indicate tobacco smoking could promote the development of cancer by affect UPR and ER associated process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concept of network biology has been widely applied to a variety of disease. Xing et al (27) indicated that specific gene modules derived from gene coexpression networks and may provide better understanding of molecular mechanisms in disease. In co-expression networks, two genes are connected and assumed to functionally interact if their expression profiles are correlated across multiple conditions.…”
Section: Discussionmentioning
confidence: 99%